2012
DOI: 10.1371/journal.pone.0032946
|View full text |Cite
|
Sign up to set email alerts
|

Identity Negative Priming: A Phenomenon of Perception, Recognition or Selection?

Abstract: The present study addresses the problem whether negative priming (NP) is due to information processing in perception, recognition or selection. We argue that most NP studies confound priming and perceptual similarity of prime-probe episodes and implement a color-switch paradigm in order to resolve the issue. In a series of three identity negative priming experiments with verbal naming response, we determined when NP and positive priming (PP) occur during a trial. The first experiment assessed the impact of tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 61 publications
2
8
0
Order By: Relevance
“…The results obtained for the control group are in line with existing literature concerning negative priming of objects, where response time is consistently slower for trials where the distractor in the prime display is identical to the subsequent probe (Tipper, 1985; de Zubicaray et al, 2006; Schrobsdorff et al, 2012). Furthermore, it has been recently established that identity or object-based negative priming is not influenced by age and the effect appears to remain constant across the lifespan (for reviews see Gamboz et al, 2002; Frings et al, 2015).…”
Section: Discussionsupporting
confidence: 88%
“…The results obtained for the control group are in line with existing literature concerning negative priming of objects, where response time is consistently slower for trials where the distractor in the prime display is identical to the subsequent probe (Tipper, 1985; de Zubicaray et al, 2006; Schrobsdorff et al, 2012). Furthermore, it has been recently established that identity or object-based negative priming is not influenced by age and the effect appears to remain constant across the lifespan (for reviews see Gamboz et al, 2002; Frings et al, 2015).…”
Section: Discussionsupporting
confidence: 88%
“…DS mediates resisting attentional capture by more salient aspects of a situation or reflexive enactment of more automatic responses to produce more deliberate and considered responses 29. When DS is impaired, as in unmedicated PD, increased motor or reflexive impulsivity is expected.…”
Section: Discussionmentioning
confidence: 99%
“…The results obtained for the control group are in line with existing literature concerning negative priming of objects, where response time is consistently slower for trials where the distractor in the prime display is identical to the subsequent probe (de Zubicaray, McMahon, Eastburn, Pringle, & Lorenz, 2006;Schrobsdorff, Ihrke, Behrendt, Herrmann, & Hasselhorn, 2012;Tipper, 1985). Furthermore, it has been recently established that identity or object-based negative priming is not influenced by age and the effect appears to remain constant across the lifespan (for reviews see Frings, Schneider, & Fox, 2015;Gamboz, Russo, & Fox, 2002).…”
Section: Discussionsupporting
confidence: 87%
“…However, it must be noted that negative priming tasks are considered to provide a measurement of an individual's ability to ignore a presented item. While there is some evidence to suggest that ignoring irrelevant stimuli is not passive in nature but does in fact require active processing (Schrobsdorff et al, 2012), the mechanisms underlying this process may differ to those recruited to suppress a prepotent verbal response (as in the HSCT). Furthermore, it has been suggested that PD participants are aided by the availability of external cueing, and that cognitive performance in this population appears to fail more consistently when internal self-cueing is required (Brown & Marsden, 1988;Dubois & Pillon, 1996;Pollux & Robertson, 2002).…”
Section: Introductionmentioning
confidence: 99%